Transcriptomic and proteomic profiling of pulmonary mucormycosis reveals a failed activation of host immune response - Zhong, Jinjin; Cai, Xiaomin; Cai, Yuchen; Zhao, Tingting; Hu, Die; Sun, Chao; Ni, Yueyan; Gu, Yu; Su, Xin (Frontiers in Immunology, 2026)
IntroductionMucormycosis is one of the most life-threatening fungal infections with delayed diagnosis and limited antifungal treatments. The transcriptome and proteome of pulmonary mucormycosis have not been fully investigated.MethodsWe obtained lung tissues and paired controls from five pulmonary mucormycosis patients and utilized transcriptomic and proteomic approaches to explore host immune response during pulmonary mucormycosis.ResultsOur transcriptomic analysis found a number of up-regulated genes and pathways associated with immune defense. These genes were related to iron metabolism, pattern recognition receptors (PRRs), cytokines, chemokines et al., which enriched in pathways involved in both innate and adaptive immunity. However, proteomic profiling revealed limited upregulation of immune-related proteins and global suppression of pathways associated with host defense, especially those related to cell junction and cytoskeletal dynamics, indicating a failed activation of host immune response.DiscussionGiven the findings of compromised immune function at infection sites, enhancing adjuvant immunotherapy and intensifying localized antifungal treatments may be beneficial for this refractory infection. Our study firstly investigated the immune landscape in pulmonary mucormycosis through combined transcriptomic and proteomic profiling, which could provide novel mechanistic insights for the prevention and treatment of pulmonary mucormycosis.